2015
DOI: 10.1016/j.jsha.2014.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Primary prevention with statins in cardiovascular diseases: A Saudi Arabian perspective

Abstract: Cardiovascular disease (CVD) constitutes one of the major causes of deaths and disabilities, globally claiming 17.3 million lives a year. Incidence of CVD is expected to rise to 25 million by 2030, and Saudi Arabia, already witnessing a rapid rise in CVDs, is no exception. Statins are the drugs of choice in established CVDs. In the recent past, evidence was increasingly suggesting benefits in primary prevention. But over the last decade Saudi Arabia has a witnessed significant rise in CVD-related deaths. Smoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…They also pointed out that the 2013 ACC/AHA guidelines may have overemphasized the statin therapy but without considering lipid targets which would lead to the inclusion of a large population for primary prevention with statins. Furthermore, this would cause overtreatment and potentially increase the incidences of statin-associated side effects and intolerance [8]. In addition, a statin prescription prevalence study reflects that the elderly population does not necessarily get the benefit from statin treatment for primary prevention of CVD [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also pointed out that the 2013 ACC/AHA guidelines may have overemphasized the statin therapy but without considering lipid targets which would lead to the inclusion of a large population for primary prevention with statins. Furthermore, this would cause overtreatment and potentially increase the incidences of statin-associated side effects and intolerance [8]. In addition, a statin prescription prevalence study reflects that the elderly population does not necessarily get the benefit from statin treatment for primary prevention of CVD [14].…”
Section: Discussionmentioning
confidence: 99%
“…The American College of Cardiology (ACC)/American Heart Association (AHA) 2013 guidelines (2013 ACC/AHA) cholesterol guidelines recommend that all patients with ASCVD should receive high-dose or moderate-dose statins therapy while ignoring lipid targets, and have recommended statin therapy to a specific group for primary and secondary prevention [7]. The 2016 European Society of Cardiology (ESC)/the European Atherosclerosis Society (EAS) (2016 ESC/EAC), the most widely used lipid management guideline, still targets lipid levels at different stages of disease activity before recommending statins [8]. Based on the 2007 Chinese Guidelines for the Management of Dyslipidemia in Adults, the 2016 Chinese guideline for the management of dyslipidemia in adults (referred to as "the new Guideline" hereafter) was released by Chinese Journal of Cardiology in 2016 formulated by a joint committee of multidisciplinary experts.…”
Section: Introductionmentioning
confidence: 99%
“…They also pointed out that the 2013 ACC/AHA guidelines may have overemphasized the use of statin while ignoring lipid targets, and would lead to the inclusion of a large population for primary prevention with statins. Furthermore, this would cause overtreatment and potentially increase the incidences of statin intolerance and sideeffects [7]. In addition, the observed statin prescribing for primary prevention in the elderly in a cohort study reflects the fact that this group may be less likely to benefit from statin treatment for primary prevention of CVD [13].…”
Section: Discussionmentioning
confidence: 99%
“…The 2016 European Society of Cardiology (ESC)/the European Atherosclerosis Society (EAS) (2016 ESC/EAC), the most widely used lipid management guideline, still target lipid levels at different stages of disease activity before recommending statins [7]. Based on the 2007 Chinese Guidelines for the Management of Dyslipidemia in Adults, the 2016 Chinese guideline for the management of dyslipidemia in adults (referred to as "the new Guideline" hereafter) was released by Chinese Journal of Cardiology in 2016 formulated by a joint committee of multidisciplinary experts.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in Saudi Arabia, which has a large number of itinerant workers, CVD is associated with smoking, high fat and low fiber intake, lack of exercise and sedentary lifestyle, in addition to a predominance of low HDL-C and high levels of triglycerides. 2 , 23 , 25 , 33 An unusually high prevalence of low HDL-C has also been observed in the Philippines, 17 which presents an intriguing dilemma for possible treatment strategies. In Indonesia, one study showed the tremendous variation in lipid profiles among the Minangkabau, Sundanese, Javanese and Buginese ethnic groups.…”
Section: Cardiovascular Disease and Dyslipidemia In Asia And The Middmentioning
confidence: 99%